Constructivist Learning Theory in Relation to Teacher Teaching Skills: Evidence from Suburban Secondary Schools in Melaka - Saleh, Hasan; Nur Afiqah Khumairah Abd Karim (Journal of TVET and Technology Review, 2026)
Constructivist Learning Theory (CLT) emphasises active knowledge construction through meaningful engagement, social interaction, and contextualised learning. This study examines the relevance of CLT in understanding the relationships among student engagement, learning environment, student motivation, and technology integration towards teacher teaching skills in suburban secondary schools in Melaka. The findings indicate each variable positively influences teaching skills: engaged students, supportive learning environments, motivated learners, and effective technology use enable teachers to implement constructivist strategies more effectively. This study contributes to theoretical and practical knowledge by linking CLT principles with teaching practice and provides recommendations for enhancing teacher competencies in suburban educational settings.